PUBLIC NARRATIVES AND ATTITUDES TOWARDS REFUGEES AND OTHER MIGRANTS: A CASE STUDY OF THE REPUBLIC OF NORTH MACEDONIA - Shushak Lozanovska, Ivona; Vasileska, Larisa (MIGRATION POLICY AND LEGAL RESPONSES, 2025)
This study examines public narratives and attitudes toward refugees and migrants in the Republic of North Macedonia within the broader historical, political, and social contexts that have shaped the country's migration landscape. The research traces migration patterns from World War II through significant regional crises, including the Bosnian conflict of the 1990s, the Kosovo crisis, and contemporary migration challenges, analyzing how these historical experiences have influenced public perception and policy formulation regarding displaced populations. The investigation focuses on contemporary public reception of migrants through systematic analysis of social media debates and political discourses. By examining social media comments on governmental statements regarding migrant acceptance, this research provides empirical insights into evolving public attitudes, identifying distinct patterns of xenophobic sentiment, solidarity expressions, and national identity-based concerns within North Macedonian society. The paper assumes that the population of North Macedonia has an exceptionally low acceptance index for migrants, with significant resistance to their integration, generally shaped by economic, cultural, and security factors. Such public attitudes are deeply rooted in unfulfilled political promises, both by national and international actors, which further exacerbates public skepticism and resistance. This study contributes to the understanding of migration discourse in the Balkans, offering recommendations for improving public attitudes and policies on migration in the context of European integration.